Editorial (2,2024) - Nain, Manjeet (Indian Journal of Extension Education, 2024)
Editorial The United Nations’ World Food Program, singled out 2023 as a record year for global food insecurity, and famines have garnered attention this year, but nevertheless ‘a pledge for transitioning away from fossil fuels in energy systems in a manner that is just orderly and equitable’ during COP28 was the historic declaration. Increasing food production efficiency on existing land, meanwhile, requires a lot of chemical fertilizer—created with fossil fuels and responsible for a large portion of agriculture’s carbon footprint. There’s a sense in which all this puts the Sustainable Development Goal targets for food and water security in conflict with one another. The technological advances to satisfy increased demand for food on a system threatened by disrupted production and shifting patterns of water availability and ensure food security without continuing to burn through finite resources to do it are to be explored. As such more must be done to address gaps to drive increased sources of capital to achieve the sustainable transformation of the food system and the extension system has to gear up with matching skills and dedicated efforts. The current issue (April-June, 2024) contains two research tools, four research notes, and fifteen full-length research papers. The full length papers focused on crafting improvement strategy for the Indian Journal of Extension Education, communication behaviour of fish farmers of the FFPO, farmers’ literacy in agriculture information, women’s involvement pattern in grain management, factors affecting adoption of climate-smart agriculture practices, export dynamics analysis of basmati rice, factors influencing ICT accessibility, perception of e-learning among students, women’s participation in financial decisions, social media addiction among the rural youth, consumer perception and awareness towards organic food, risk perception and perceived effects on environment vis-à-vis dairy animal waste management, factors affecting on adoption of sustainable agricultural practices, challenges of online education among senior secondary students and analysis of wool supply chain. The research tools to measure the abilities of rural women towards entrepreneurship, and measuring attitude of fish farmers towards the APART project were included, whereas constraints faced by paddy farmers in adoption of climate smart agricultural practices, problems faced by the farmers in post-harvest management of pomegranate, factors influencing milk marketing channel strategies and analysis of demonstrations on rapeseed made the ‘research note’ section During the quarter, the NAAS announced its rating 2024 where, the Indian Journal of Extension Education even after getting accepted for indexing in SCOPUS database, could not get matching score in rating but nevertheless it is being indexed in almost all major databases which includes; SCOPUS, CAB International, AGRIS, Index Copernicus International, Plum X, Medley, SCILIT, UGC-CARE List, Crossref, Semantic Scholar, World Cat, EBSCO, etc. I on behalf of the editorial board extend my sincere thanks to all those who directly or indirectly assisted the team editorial board. Present one is 14th issue of the Indian Journal of Extension Education by the present editorial board with all possible positive changes without compromising the punctuality and quality. The ISEE elections are in progress and soon new Editorial Board may be in vogue. We acknowledge Ms ACS publisher for maintaining timeline. All the expert members of the editorial board, the reviewing contributions, and willful contributors of authors are sincerely acknowledged. The support extended by Executive Council is duly acknowledged. Special thanks are extended to Dr. U.S. Gautam, Dr. Rashmi Singh, Dr. B. K. Singh and Dr. J.S. Malik for their insightful thoughts and guidance. Dr. Bhanu P. Mishra, Vice President (Central Zone) deserves special thanks for making committed efforts at all stages of ISEE matters. (Manjeet Singh Nain)